Local anesthetic wound infusion versus standard analgesia in paediatric post-operative pain control : a randomised control trial - Machoki, Mugambi Stanley (Division of Paediatric Surgery, 2015)
Post-operative analgesia currently relies on multimodal therapy including epidural analgesia, intravenous morphine and/or paracetamol (Perfalgan ®) infusion. Local wound infusion has been effectively utilized in adults with promising results but has not been prospectively tested in children undergoing different abdominal operations. The aim of this study was to compare continuous local anesthetic wound infusion to the current standard of care in post-operative pain control in children. Methods: We conducted a prospective randomized, pain assessor blinded trial comparing Bupivacaine wound infusion {Continuous Local Anaesthetic Wound Infusion - CLAWI) in addition to intravenous paracetamol (Perfalgan®) and morphine for rescue analgesia. This was compared to: (a) epidural bupivacaine plus intravenous morphine and Perfalgan® [EPI] for children undergoing open abdominal surgery and (b) intravenous morphine and Perfalgan® infusion alone [standard post-operative analgesia - SAPA] in children undergoing Lanz incision laparotomy for complicated appendicitis. Patients aged between 3 months and 12 years undergoing laparotomy or open appendectomy were randomly selected for local anesthetic wound infusion (CLAWI) versus EPI or CLAWI versus (SAPA) respectively. Exclusion criteria were neurological impairment, post-operative ventilation and history of adverse reaction to bupivacaine. Consent from the guardian, assent from patients above the age of 7 years and ethics approval from the University of Cape Town Human Ethics Research Committee was obtained. The wound infusion catheter ('lnfiltralLong', PANJUNK®) was placed sub-fascially after suture of the peritoneum and 0.2 % bupivacaine 2mls/kg infused on anesthetic reversal followed by 0.2ml/kg/hour thereafter for 48 hours. Pain assessments were performed for each patient at regular intervals by a single assessor who had training in pediatric pain management and who was blinded to the group allocation. The duration of surgery, length of incision, perioperative antibiotics, wound class risk of surgical site infection, time to return to full feeds, drug reactions; hospital stay, surgical site infection and wound catheter and epidural catheter complications were recorded for each patient. Primary outcome measure was total morphine used in the appendectomy-SAPA vs appendectomy-CLAW! group and rescue morphine requirements in the laparotomy-EPI vs laparotomy-CLAWI group. The secondary outcomes were pain control as measured using the FLACC scale, time to full feeds, mobilization and requirement for urinary catheter.